Requirements Engineering for Data Products: Adapting User Stories - Maestre-Góngora, Gina; Gómez-Álvarez, María Clara (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2026)
This paper proposes recommendations for adapting user stories as a tool for capturing and managing requirements that support data-based functionalities (dashboards, AI models, among others). To conclude, aspects such as collaboration between roles, verifiable acceptance criteria, integration with model metrics, and support for data science tools and algorithms are considered.